Abdominopelvic tumor due to actinomycosis in a pregnant woman - Vásquez Alva, Rolando (2018)
Actinomycosis is a rare infection caused by Actinomyces spp, a gram-positive germ of saprophytic nature, located in the mouth, genital tract and lower gastrointestinal tract. Its diagnosis is difficult because of its low frequency and variable clinical presentation. We report the case of a 28-year-old female, 34½ weeks pregnant, who presented a pelvic and hypogastric mass accompanied by abdominal pain. One day before admission, the contraction-like pain in the right iliac fossa intensified. The patient underwent a cesarean section and a full-term product was obtained. This surgery was followed by hysterectomy and resection of an abdominal wall tumor as well as en bloc resection of the vesical dome plus appendectomy. The pathology report informed actinomycosis. We focus on the presentation in a pregnant woman with a preterm and live product, as well as the signs and symptoms that help consider this diagnosis.